Population attributable fraction of risk factors for low birth weight in the Japan Environment and Children's Study. (December 2022) - Nishihama, Yukiko; Nakayama, Shoji F.; Tabuchi, Takahiro; ,
Highlights: Population attributable fraction (PAF) for low birth weight was estimated for multiple factors. A total of 91, 559 mother–child dyads were included in the study. The highest single PAF for low birth weight was inadequate gestational weight gain. The number of low birth weight can be reduced by 27% by preventing lead and tobacco exposure. Abstract: Background: Low birth weight (LBW), which is considered a birth weight of <2500  g, poses significant health problems for children. However, population attributable fraction (PAF) of risk factors for LBW have not been well studied. Objective: We aimed to re-evaluate associations between risk factors for LBW reported in previous studies that used the Japan Environment and Children's Study (JECS) data, and to estimate the magnitude of risk using PAF. Methods: Data including 91, 559 mother–child dyads were obtained from JECS. Risk factors identified by previous studies that used JECS data were used to calculate odds ratios for LBW using a Bayesian logistic regression model. Based on calculated odds ratios, the PAF was calculated. Results: Parity, history of adenomyosis, hypertension disorder of pregnancy, maternal age at birth, prepregnancy body mass index, gestational weight gain (GWG), maternal smoking and lead (Pb) exposure were all significantly associated with LBW. The sum of the PAF of all factors was 79.4 %, with the largest PAF among single risk factors being GWG (16.5 %); the environmental portion of the PAF (Pb exposure, 14.6 % + maternal smoking, 12.1 %) surpassed the PAF of GWG. Conclusion: Our findings suggest that the number of births classified as LBW can be reduced by approximately 27% if Pb exposure is reduced to the lowest quartile and maternal smoking is eliminated. Further investigations are needed to identify unknown risk factors for LBW.